Fictive Deixis, Direct Discourse, and Viewpoint Networks - Dancygier, Barbara (Frontiers in Communication, 2021)
This paper proposes a renewed and more textured understanding of the relation between deixis and direct discourse, grounded in a broader range of genres and reflecting contemporary multimodal usage. I re-consider the phenomena covered by the concept of deixis in connection to the speech situation, and, by extension, to the category of Direct Discourse, in its various functions. I propose an understanding of Direct Discourse as a construction which is a correlate of Deictic Ground. Relying on Mental Spaces Theory and the apparatus it makes available for a close analysis of viewpoint networks, I analyze examples from a range of discourse genres - textual, visual and multimodal, such as literature, political campaigns, internet memes and storefront signs. These discourse contexts use Direct Discourse Constructions but usually lack a fully profiled Deictic Ground. I propose that in such cases the Deictic Ground is not a pre-existing conceptual structure, but rather is set up ad hoc to construe non-standard uses of Direct Discourse–I refer to such construals as Fictive Deictic Grounds. In that context, I propose a re-consideration of the concept of Direct Discourse, to explain its tight correlation with the concept of deixis. I also argue for a treatment of Deictic Ground as a composite structure, which may not be fully profiled in each case, while participating in the construction of viewpoint configurations.